Fintech and Microfinance: Empowering Local Entrepreneurs for Sustainable Growth - Ferdi Nazirun Sijabat; Safiah; Banta Karollah; Muhammad (Seumike : Society Progress Journal, 2025)
The issue of limited financial inclusion continues to hinder sustainable growth among micro-entrepreneurs in developing regions. This study explores the integration of Fintech and microfinance as a solution to enhance digital financial access, entrepreneurial capacity, and community resilience. The research focuses on a hybrid community engagement program jointly organized by KABA Academic Society (Indonesia) and KRIRK University (Thailand) in Soi Ram Intra, Bangkok. Using a participatory action research approach, the program was implemented through needs assessment, development of appropriate technologies, hybrid training, and short-term impact evaluation. The results showed significant improvements in digital literacy, business management skills, and environmental awareness among local participants. Community members learned to adopt digital marketing tools and simple composting technologies, which directly supported both economic and ecological sustainability. The hybrid model enabled inclusive access and knowledge transfer across diverse participants. The study concludes that combining Fintech solutions with microfinance frameworks in a community-based, cross-cultural initiative can empower local entrepreneurs and support long-term sustainable development goals.